Extent of Readiness of Automobile Technology Educators to Utilize Artificial Intelligence in Colleges of Education in South East, Nigeria - Wogu, Sunday Nwabueze; Okorafor, Anthony Osinachi; Okoye, Peter Izuoba; Okeke, Nwankwo Chima (Journal of Research in Industrial Technology and Educational Studies, 2025)
The utilisation of Artificial Intelligence (AI) into educational practices has significantly transformed various disciplines, including Automobile Technology Education (ATE). This study addresses the readiness of educators to utilise AI within ATE in Nigerian colleges of education. In order to conduct this study, one research question and two hypotheses were formulated using descriptive survey research design. A population of 68 automobile technology educators in public colleges of education in South East, Nigeria was studied. A researcher-designed questionnaire containing 10 items with a reliability coefficient of 0.79 was used for data collection. Mean and standard deviation were used to answer the research question while t-test was used to test the null hypotheses at 0.05 level of significance. Findings of the study revealed that automobile technology educators have low extent of readiness to utilise AI in colleges of education in South East, Nigeria. Automobile technology educators in colleges of education in South East, Nigeria do not differ significantly in their mean ratings on the extent of readiness to utilise AI based on ownership type and gender. Conclusion and recommendations were suggested for the study.
Keywords: Colleges of education; automobile technology education; readiness